PERAN BKPSDM KOTA CIMAHI DALAM PEMBINAAN DISIPLIN ASN DI LINGKUNGAN PEMERINTAH KOTA CIMAHI - Neneng Mastoah (Universitas Jenderal Ahmad Yani, 2025)
This study examines the role of BKPSDM Cimahi in fostering civil service discipline. This study aims to examine the role of the Human Resources Development and Personnel Agency (BKPSDM) of Cimahi City in fostering civil service discipline. emphasizing how discipline is interpreted, negotiated, and experienced by the actors involved. Employing a qualitative case study approach. data were collected through in-depth interviews with civil servants, BKPSDM officials, and service users, complemented by participatory observation of service activities and organizational documents. The findings reveal three major themes: first. civil service discipline is understood as an arena of role conflict and ambiguity, where officials must balance procedural compliance with responsiveness to public needs; second, the effectiveness of disciplinary guidance is strongly shaped by perceptions of Procedural Justice and the emotional experiences of civil servants, influencing long-term compliance; third, the integration of digital technologies enhances transparency yet risks being perceived merely as surveillance if not accompanied by a human-centered approach. These insights enrich Role Theory by adding an institutional dimension in managing role conflicts, and extend disciplinary literature by emphasizing subjective meaning and emotional experiences. Practically. the study underscores the importance of balancing regulatory control, procedural fairness, and trust ecology in disciplinary management, while also opening new avenues for exploring the nexus between discipline, technology, and professional identity within local governance contexts.